Optimal. Leaf size=26 \[ 6-\left (e^{3+e^{-x^2} x}-x\right )^2 x^2 \]
________________________________________________________________________________________
Rubi [A] time = 0.88, antiderivative size = 24, normalized size of antiderivative = 0.92, number of steps used = 3, number of rules used = 3, integrand size = 100, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.030, Rules used = {6741, 12, 6687} \begin {gather*} -\left (e^{e^{-x^2} x+3}-x\right )^2 x^2 \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 6687
Rule 6741
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int 2 e^{-x^2} \left (e^{3+e^{-x^2} x}-x\right ) x \left (-e^{3+e^{-x^2} x+x^2}+2 e^{x^2} x-e^{3+e^{-x^2} x} x+2 e^{3+e^{-x^2} x} x^3\right ) \, dx\\ &=2 \int e^{-x^2} \left (e^{3+e^{-x^2} x}-x\right ) x \left (-e^{3+e^{-x^2} x+x^2}+2 e^{x^2} x-e^{3+e^{-x^2} x} x+2 e^{3+e^{-x^2} x} x^3\right ) \, dx\\ &=-\left (e^{3+e^{-x^2} x}-x\right )^2 x^2\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.70, size = 24, normalized size = 0.92 \begin {gather*} -\left (e^{3+e^{-x^2} x}-x\right )^2 x^2 \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [B] time = 0.61, size = 49, normalized size = 1.88 \begin {gather*} -x^{4} + 2 \, x^{3} e^{\left ({\left (x + 3 \, e^{\left (x^{2}\right )}\right )} e^{\left (-x^{2}\right )}\right )} - x^{2} e^{\left (2 \, {\left (x + 3 \, e^{\left (x^{2}\right )}\right )} e^{\left (-x^{2}\right )}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} \int -2 \, {\left (2 \, x^{3} e^{\left (x^{2}\right )} - {\left (2 \, x^{4} - x^{2} - x e^{\left (x^{2}\right )}\right )} e^{\left (2 \, {\left (x + 3 \, e^{\left (x^{2}\right )}\right )} e^{\left (-x^{2}\right )}\right )} + {\left (2 \, x^{5} - x^{3} - 3 \, x^{2} e^{\left (x^{2}\right )}\right )} e^{\left ({\left (x + 3 \, e^{\left (x^{2}\right )}\right )} e^{\left (-x^{2}\right )}\right )}\right )} e^{\left (-x^{2}\right )}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [B] time = 0.08, size = 50, normalized size = 1.92
method | result | size |
risch | \(-x^{4}+2 \,{\mathrm e}^{\left (3 \,{\mathrm e}^{x^{2}}+x \right ) {\mathrm e}^{-x^{2}}} x^{3}-{\mathrm e}^{2 \left (3 \,{\mathrm e}^{x^{2}}+x \right ) {\mathrm e}^{-x^{2}}} x^{2}\) | \(50\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} -x^{4} - 2 \, \int -{\left (2 \, x^{4} e^{6} - x^{2} e^{6} - x e^{\left (x^{2} + 6\right )}\right )} e^{\left (-x^{2} + 2 \, x e^{\left (-x^{2}\right )}\right )}\,{d x} + 2 \, \int -{\left (2 \, x^{5} e^{3} - x^{3} e^{3} - 3 \, x^{2} e^{\left (x^{2} + 3\right )}\right )} e^{\left (-x^{2} + x e^{\left (-x^{2}\right )}\right )}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.65, size = 39, normalized size = 1.50 \begin {gather*} 2\,x^3\,{\mathrm {e}}^3\,{\mathrm {e}}^{x\,{\mathrm {e}}^{-x^2}}-x^4-x^2\,{\mathrm {e}}^6\,{\mathrm {e}}^{2\,x\,{\mathrm {e}}^{-x^2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [B] time = 16.64, size = 42, normalized size = 1.62 \begin {gather*} - x^{4} + 2 x^{3} e^{\left (x + 3 e^{x^{2}}\right ) e^{- x^{2}}} - x^{2} e^{2 \left (x + 3 e^{x^{2}}\right ) e^{- x^{2}}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________